Trade and investment in the Caribbean Basin since the CBI. - Coppin, Addington (1992)
Suggests some marginal effects on the region's overall economic performance, with more pronounced benefits for Central America and the Central Caribbean region than for the rest of the Caribbean. Calls for substantially more investment if the CBI is to be successful in attaining the goals of economic revitalization and diversification in the region.